Early Morphea Simulating Patch-Stage Mycosis Fungoides. (May 2015) - Fujimoto, Masakazu; Basko-Plluska, Juliana L.; Petronic-Rosic, Vesna; Shea, Christopher R.
Abstract : Abstract: Morphea is a rare fibrosing condition of the skin and underlying tissues characterized histopathologically by thickened collagen bundles throughout the dermis, loss of adnexal structures, and "fat trapping." In the early stages of morphea, the absence of the fully developed characteristic findings may cause diagnostic confusion for the practicing pathologist. The authors report an unusual case of early morphea misdiagnosed as patch-stage poikilodermatous mycosis fungoides (MF) based on the initial clinical, histopathologic, and molecular findings. However, as time elapsed, well-developed lesions revealed clinical and histopathologic features diagnostic of morphea. The authors report this case to illustrate that lesions of early morphea may simulate MF. Given the similarities in clinicopathologic presentation, dermatologists and dermatopathologists should be cautious not to inadvertently misinterpret early morphea as MF.